Technologies, Episteme and Subjectification in a Regime of Health Guarantees [Tecnologías, Episteme y Subjetivación en Un Régimen de Garantías en Salud] - Castillo-Sepulveda, J; Tapia-Farias, J (Pontificia Universidad Catolica de Valparaiso, 2017)
We analyze the emerging governmentality in the last health reform in Chile: the Regime of Explicit Guarantees in Health. This form of government interweaves schemes of knowledge legitimization and biomedical actions prioritization guided by Evidence-Based Medicine and other criteria, reorienting the activities of government to redefine the status some biological functions. We have defined as biogovernmentality the field of possibilities that promotes the articulation between biomedicine and processes of government. For the analysis proposed, we employ resources from actor-network theory, the account of the processes of enactment in the articulation of the regime. This, after the deployment of focused ethnographies at various levels of public and private health services, and interviews with expert designers and professionals. The analysis expresses technological objects (prioritizators, clinical practice guidelines, benefit packages, computer systems) and epistemic things (prioritization interweaves, acceleration regimes and somatocracy) that produce a specific mode of somatic subjectification, which reconfigures the subject as a space of government based on organs and body physiology.